2018
DOI: 10.1039/c8cp03753a
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced dissociation of sodiated glucose, galactose, and mannose, and the identification of anomeric configurations

Abstract: Collision-induced dissociation of sodiated α-glucose, β-glucose, α-galactose, β-galactose, α-mannose, and β-mannose was studied using electronic structure calculations and resonance excitation in a low-pressure linear ion trap. We made an extensive search of conformers and transition states in calculations to ensure the transition state with the lowest barrier height for each dissociation channel could be located. The major dissociation channels, in addition to desodiation, are cross-ring dissociation and dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(117 citation statements)
references
References 49 publications
3
113
1
Order By: Relevance
“…Identifications of monosaccharides calculations have revealed that the water elimination barriers of the O1 and O2 atoms in the cis configuration of the sodium adduct was substantially smaller than that in the trans configuration. 41,42 We found lithium adducts have the similar properties. Therefore, the CID spectrum with high ion m/z 169 intensity, representing a high branching ratio in the dehydration reaction, can be assigned to the anomer that has the O1 and O2 atoms in the cis configuration (α-glucose, α-galactose, and β-mannose).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Identifications of monosaccharides calculations have revealed that the water elimination barriers of the O1 and O2 atoms in the cis configuration of the sodium adduct was substantially smaller than that in the trans configuration. 41,42 We found lithium adducts have the similar properties. Therefore, the CID spectrum with high ion m/z 169 intensity, representing a high branching ratio in the dehydration reaction, can be assigned to the anomer that has the O1 and O2 atoms in the cis configuration (α-glucose, α-galactose, and β-mannose).…”
Section: Resultsmentioning
confidence: 55%
“…39,40 In this study, we extended the use of cross ring fragments to identify the linkage positions and anomeric configurations of disaccharides containing glucose, galactose, mannose, GalNAc, and GlcNAc based on the understanding of dissociation mechanism. [41][42][43] The third one is the capability to dissociate selective chemical bond and generate the chosen monosaccharide or disaccharide for subsequent structural determination. We have developed a procedure, namely logically derived sequence (LODES) for tandem MS, to generate the desired monosaccharide or disaccharide by collision induced dissociation of oligosaccharide sodium adducts.…”
Section: Introductionmentioning
confidence: 99%
“…A major difference between the CID spectra of two anomers of a given hexose (e.g., Figure B and C for α‐ and β‐glucose, respectively) is the relative intensity of ion m / z 169, which represents H 2 O elimination. High‐level quantum chemistry calculations have revealed that the water elimination barriers of the O1 and O2 atoms in the cis configuration of the sodium adduct were substantially smaller than that in the trans configuration . We found that lithium adducts had similar properties.…”
Section: Resultsmentioning
confidence: 71%
“…These crossed‐ring fragmentation patterns (e.g., loss of m / z 120, 90, 60) were explained by the retro‐aldol reaction . Recent high‐level quantum chemistry calculations confirmed that the retro‐aldol reaction, starting from the O1 atom of the sugar at the reducing end is the dominant mechanism of cross‐ring dissociation. This mechanism does not depend on the orientation of hydroxyl groups or the sugar connecting to the hydroxy groups at the nonreducing end.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation